On Beckmann's sispersed "interaction city" - John Hartwick; Andrei Bazhanov (Queen's University, Department of Economics, 2007)
Beckmann;s interaction model has each resident touching base in face-to-face activity with every other resident, per unit time, at the other's residence. We re-work his resulting interaction city with each resident operating with a Cobb-Douglas utility function. We then turn to a more satisfactory technology of residents interacting and solve for an interaction city with an explicit payoff to resident i for engaging in interaction.
Keywords: D11; R14; 330; spatial interactions of city residents; productive face-to-face activity; Stadtökonomik; Kommunikation; Kooperation; Nutzenfunktion